PEMBELAJARAN MENULIS TEKS DRAMA DENGAN MENGGUNAKAN METODE PICTURE AND PICTURE - Pipin Supini; Rochmat Tri Sudrajat; Heri Isnaini (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2021)
The learning of writing drama texts is generally less attractive to students because of the difficulty of students starting the writing process and developing words into appropriate sentences. This research was conducted to examine learning to write drama texts using the picture and picture method in class XI students at SMAN 1 MANIIS. The formulation of the problem in this study is the difficulty experienced by students in learning to write drama texts. This study aims to describe learning to write drama texts using the picture and picture method and to answer the problem formulation. This research method uses descriptive qualitative and uses data collection techniques in the form of writing skills tests. Based on the results of research conducted on students of class XI with a total of 20 students during the learning process, it shows that there is an increase in the average score obtained by students, the initial test gets an average score of 61 and the final test gets an average score of 75.5. These results indicate an increase in each test.